Enhancing Job Performance: Mindfulness Among Public Hospital Nurses in South Africa - Mosutoa Monyai; Nghamula Nkuna; Hlanganipai Ngirande; Wiza Munyeka (Management)
Research Question The study’s purpose was to investigate the relationship between mindfulness and job performance among public hospital nurses in Polokwane Local Municipality, South Africa. Motivation: This study examines public hospital nurses’ mindfulness and job performance and the nature of this relationship. The study is one of the first to investigate the relationship between mindfulness and job satisfaction among South African nurses and addresses a discernible dearth of knowledge about mindfulness and job satisfaction. Idea: The idea behind this study is to model the relationship between mindfulness and job performance in view of the fact that nurses work in stressful conditions that require them to balance how they conduct their work and also being mindful that they are working with people afflicted by health challenges. Data: A cross-sectional deductive design with 1287 nurses from Polokwane Local Municipality’s three public hospitals was used in conjunction with the positivist paradigm and a quantitative approach. A stratified random sampling method was used with a recommended sample size of 297 nurses divided into professional and assistant nurses determined by the Raosoft sample size calculator. Tools: Data collection utilised a self-administered questionnaire and the analysis was done by the Statistical Package for Social Sciences (SPSS) version 28, using the Hayes Process add-in software for mediation. Findings: The findings indicate a relationship between mindfulness and job performance among Polokwane Local Municipality public hospital-based nurses (r=.393**; p=.000). Mindfulness influences job performance = 1.09, + (298) = 1.09, p = .000, according to the regression results.